2016
DOI: 10.3906/kim-1506-37
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and theoretical approaches for structural and mechanical properties of novel side chain LCP-PP graft coproducts

Abstract: The monomers p-biphenyloxycarbonylphenyl acrylate (BPCPA) and p-biphenyloxycarbonylphenyl methacrylate (BPCPMA) were synthesized by the reaction of p-acryloyloxybenzoyl chloride and p-methacryloyloxybenzoyl chloride with 4-hydroxybiphenyl, respectively, and polymerized by bulk polymerization in vacuum by using dicumyl peroxide. The graft copolymerization of the monomers onto polypropylene were carried out by bulk melt polymerization at 170 • C with various concentration levels of the monomers and the initiator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…In addition to that, it is known that the groups presenting in the grafted units affect highly the crucial characteristics of the thermoplastics such as IPP. 10,11 Namely, liquid crystalline polymer (LCPs) with their remarkably rigid, rod-like, and stiff molecular backbone causes to form well-ordered structure and better arrangement with dimensional stability in the polymer matrix by forming highly orientations and alignments. Moreover, the existence of LCPs in the polymer matrix, which gains the ability to show the anisotropic behavior due to the underlying or subunit groups called as mesogens, leads to significant advance in the mechanical performance by means of their comparatively higher load capacity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to that, it is known that the groups presenting in the grafted units affect highly the crucial characteristics of the thermoplastics such as IPP. 10,11 Namely, liquid crystalline polymer (LCPs) with their remarkably rigid, rod-like, and stiff molecular backbone causes to form well-ordered structure and better arrangement with dimensional stability in the polymer matrix by forming highly orientations and alignments. Moreover, the existence of LCPs in the polymer matrix, which gains the ability to show the anisotropic behavior due to the underlying or subunit groups called as mesogens, leads to significant advance in the mechanical performance by means of their comparatively higher load capacity.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to that, it is known that the groups presenting in the grafted units affect highly the crucial characteristics of the thermoplastics such as IPP 10,11 . Namely, liquid crystalline polymer (LCPs) with their remarkably rigid, rod‐like, and stiff molecular backbone causes to form well‐ordered structure and better arrangement with dimensional stability in the polymer matrix by forming highly orientations and alignments.…”
Section: Introductionmentioning
confidence: 99%
“…The thermograms of virgin IPP and the composites containing varying contents (5, 10, 15, 20 and 30) and sizes (45 and 75 µm) of ulexite were depicted graphically in Figure 1. The endothermic heat flows appearing at both figures was attributed to the melting of IPP crystalline domains [37]. Moreover, the results showed that the crystalline melting temperatures of IPP were highly depended on both the contents and size of the ulexite presenting in the IPP matrix.…”
Section: 1thermal Analysis Of Ipp Based Compositesmentioning
confidence: 86%
“…The I.R. vibrations at ~700 and 840 cm -1 were due to out-of-plane bending vibrations of C-H bonds in vinylic groups [26]. As the temperature increased, the I.R.…”
Section: Tga/ftir Analysis Of Homopolymer Poly(abcf13)mentioning
confidence: 97%